Quantitative cytological methods in the differential diagnosis of carcinoma in situ and cervical dysplasia - Vega Rizo Patron, Leoncio (2015)
The authors have studied the degree of histopathological correlation between biopsic and cytological examinations of displasias of the cervix. They found the counting of the total number of atypical cells is a very long procedure of little practical utility. More useful was the differentia percentual counting of the typical cells divided in four groups: basal, parabasal, intermediates and superficials. The measurement af the cellular and nuclear diameters showed that the displasias exist and increase of the cellular surface area. In the nuclear areas no significative variations were found. In the displasias the nuclear cromatines had a moderately irregular appearance while in the cases of carcinoma "in situ" the nuclear chromatin had a gross, irregular aspect In the cases of displasia and carcinoma "in situ" the cytological picture was of a diminished percent of intermediate cells with an increase of the basal and parabasal atypical cells.